Chromosomal Rearrangements and Satellite DNAs: Extensive Chromosome Reshuffling and the Evolution of Neo-Sex Chromosomes in the Genus Pyrrhulina (Teleostei; Characiformes) - de Moraes, Renata Luiza Rosa (2023)
Chromosomal rearrangements play a significant role in the evolution of fish genomes, being important forces in the rise of multiple sex chromosomes and in speciation events. Repetitive DNAs constitute a major component of the genome and are frequently found in heterochromatic regions, where satellite DNA sequences (satDNAs) usually represent their main components. In this work, we investigated the association of satDNAs with chromosome-shuffling events, as well as their potential relevance in both sex and karyotype evolution, using the well-known Pyrrhulina fish model. Pyrrhulina species have a conserved karyotype dominated by acrocentric chromosomes present in all examined species up to date. However, two species, namely P. marilynae and P. semifasciata, stand out for exhibiting unique traits that distinguish them from others in this group. The first shows a reduced diploid number (with 2n = 32), while the latter has a well-differentiated multiple X1X2Y sex chromosome system. In addition to isolating and characterizing the full collection of satDNAs (satellitomes) of both species, we also in situ mapped these sequences in the chromosomes of both species. Moreover, the satDNAs that displayed signals on the sex chromosomes of P. semifasciata were also mapped in some phylogenetically related species to estimate their potential accumulation on proto-sex chromosomes. Thus, a large collection of satDNAs for both species, with several classes being shared between them, was characterized for the first time. In addition, the possible involvement of these satellites in the karyotype evolution of P. marilynae and P. semifasciata, especially sex-chromosome formation and karyotype reduction in P. marilynae, could be shown.